The Impact of Work Discipline and Work- life Balance on Work Productivity at Mercure Hotel, Jakarta - Lestari, Sri Sayekti (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research aims to identify the impact of work discipline and work-life balance on work productivity at the Sintesa Mercure Hotel Jakarta. Data was collected through the use of a questionnaire filled in by 70 respondents and then analyzed using correlation coefficients and regression analysis. From the research results, it was revealed that work productivity at the Sintesa Mercure Hotel Jakarta is influenced positively and significantly by work discipline and work-life balance. The recommendation from this research is that companies continue to facilitate employees in efforts to improve work discipline and work-life balance, so as to increase overall work productivity.